1981
DOI: 10.1103/physrevb.23.383
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate phases in barium sodium niobate

Abstract: The x-ray-diffraction spectra of Ba2NaNb50&5 have been investigated by means of i precession camera between room temperature and 500'C, across the orthorhombic-tetragon il transition near Tt =300'C. Long exposures have revealed reflections, onsetting with the orthorhombic phase, which are incommensurate with respect to the periodicity of the basic crystal lattice.Referred to the pseudotetragonal lattice vectors, the modulation vector is k = (1+5)(a + b )/ 4+e /2 where 5 increases, on heating, from a value of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 30 publications
4
42
1
Order By: Relevance
“…The occupational disorder has been identified as the cause of the structural modulation and related to the incommensurable character found in the TTB compounds. [7][8][9][10][11] It may be expected that the unusual dielectric properties of CBN and its phase-transition behavior are associated with disordered states of the incommensurate ͑ICS͒ tetragonal phase. Recently we observed normal-torelaxor ferroelectrics transition around 252°C and macrodomain-to-microdomain switching in CBN-28 crystals.…”
mentioning
confidence: 99%
“…The occupational disorder has been identified as the cause of the structural modulation and related to the incommensurable character found in the TTB compounds. [7][8][9][10][11] It may be expected that the unusual dielectric properties of CBN and its phase-transition behavior are associated with disordered states of the incommensurate ͑ICS͒ tetragonal phase. Recently we observed normal-torelaxor ferroelectrics transition around 252°C and macrodomain-to-microdomain switching in CBN-28 crystals.…”
mentioning
confidence: 99%
“…8,11,13 ED patterns have revealed a superlattice through the ͓110͔ zone exhibiting structural variations respect to the TTB cell, promoted by the collective shearing of the oxygen octahedra, provoking a structural variation along c ͑supercell͒. The succession of reflections does not show equal separation in the superlattice plane, which gives the incommensurable character in the system LSBNT.…”
Section: Discussionmentioning
confidence: 94%
“…A fourth vector is needed, the modulation wave vector kϭ͓(1ϩ␦)/4͔a*ϩ͓(1ϩ␦)/4͔b*ϩ͓c*/2͔, that takes into account the incommensuration parameter ␦. 11 The extra spots are actually situated at positions ͓h,k,l͔͑1/4ϩ␦, 1/4ϩ␦, 1 2 ͒ and ͓h,k,l͔͑3/4ϩ3␦, 3/4ϩ3␦, 1 2 ͒.…”
Section: B Analysis By Electron Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] Simon et al [48] showed that SBN crystals exhibit anisotropic dielectric behavior. They behave as relaxors along the [001] direction and as ferroelectrics along the [100] direction; such features are possibly related to the existence of structural modulations.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%